Anesthetist‐delivered intraoperative transesophageal echocardiography in pediatric cardiac surgery. Issue 5 (4th February 2019) - Murphy, Tim
Summary: This article reviews the evidence for anesthetist‐delivered perioperative transesophageal echocardiography for children undergoing cardiac surgery. It addresses the additional issues of training, developing practice, accreditation, and the requirement for collaboration with pediatric cardiologists, surgeons and other members of the perioperative team. Finally an overview of the potential structure of an anesthetist‐delivered perioperative transesophageal echocardiography service is presented.